Role of omalizumab in insulin hypersensitivity: a case report and review of the literature. Issue 5 (16th April 2018) - Mishra, S.; Connors, L.; Tugwell, B.
Abstract: Background: Insulin allergy is a rare yet severe side effect of exogenous insulin use. Management typically involves use of alternative antihyperglycaemic agents, symptom control with antihistamines, use of different insulin formulations, and induction of tolerance with incremental doses of insulin. This treatment regimen is not always successful, and the use of omalizumab, an anti‐IgE monoclonal antibody, has been used to induce tolerance to insulin. Case report: G.M. is a 62‐year‐old man with Type 2 diabetes mellitus. His condition was not optimized on oral agents, and insulin therapy was required. G.M. had anaphylaxis to insulin NPH, and subsequent skin‐prick testing was positive to insulin aspart, insulin NPH, insulin glulisine, insulin detemir, regular insulin, insulin glargine 100 units/ml and insulin glargine 300 units/ml. He received incremental doses of several insulin formulations; however, he experienced diffuse urticaria preventing optimal glycaemic control. Three successful cases have been described in the literature of omalizumab inducing tolerance to exogenous insulin; therefore, G.M. was started on omalizumab. He subsequently tolerated treatment doses of insulin glulisine and insulin detemir with no allergic reactions and with improvement in glycaemic control. Conclusion: To our knowledge, this is the first described case of allergy to insulin glargine 300 units/ml and reiterates the potential use of omalizumab in insulin allergy. Further research is warranted to determine if omalizumab should be considered standard of care in difficult‐to‐treat insulin hypersensitivity. What's new?: This paper describes a novel therapy, omalizumab use, that may be useful in difficult‐to‐treat insulin allergy. The paper describes the first reported hypersensitivity reaction to insulin glargine 300 units/ml.